Survodutide for treatment of obesity: baseline characteristics of participants in a randomized, double-blind, placebo-controlled, phase 3 trial (SYNCHRONIZE-1) - Le Roux, Carel W.; Wharton, Sean; Bozkurt, Biykem; Platz, Elke; Bleckert, Gabriele; Ajaz Hussain, Samina; Brückmann, Martina; Startseva, Elena; Kloer, Isabel M.; Kaplan, Lee M. (Diabetes, obesity and metabolism, 2025)
Aims Survodutide, a novel glucagon receptor and glucagon-like peptide-1 (GLP-1) receptor dual agonist, elicited significant weight loss in a phase 2 trial in individuals with obesity without type 2 diabetes (T2D). Two multinational phase 3 trials are investigating survodutide for obesity management in individuals with or without T2D. We report the baseline characteristics of participants in the SYNCHRONIZE-1 trial in adults with obesity without T2D (ClinicalTrials.gov: NCT06066515). Materials and methods Participants aged ≥18 years with BMI ≥30 or ≥27 kg/m2 with ≥1 obesity complication without T2D were randomized 1:1:1 to double-blind, once-weekly, subcutaneous injections of survodutide (up-titrated to 3.6 or 6.0 mg) or placebo for 76 weeks. The primary endpoints are percent body weight change and achievement of body weight reduction ≥5% from baseline to Week 76. Efficacy and safety analyses will include all randomized and treated participants. Results At baseline, participants (n = 725 from 14 countries) had a mean age of 47.1 years, BMI 37.9 kg/m2, and waist circumference 115.2 cm. Most participants (59.4%) were female; 47.3% were from North America, 21.0% from Europe, and 20.0% from East Asia. Obesity complications included hypertension (40.0%), dyslipidaemia (33.7%), and prediabetes (30.2%). Mean haemoglobin A1c was 5.5%, estimated glomerular filtration rate 93.0 mL/min/1.73 m2, systolic/diastolic blood pressure 127.0/82.7 mmHg, and low-density lipoprotein cholesterol 116.4 mg/dL; 21.8% were taking lipid-lowering drugs. Conclusions SYNCHRONIZE-1 will determine the efficacy, safety, and tolerability of survodutide, a glucagon receptor/GLP-1 receptor dual agonist, for weight loss in a representative cohort of people with obesity without T2D.